Hubungan antara Tayangan Erotika di Pornomedia terhadap Perilaku Seksual Siswa - Cahyani, Zunita Nur; Radjah, Carolina Ligya; Lasan, Blasius Boli (Jurnal Kajian Bimbingan dan Konseling, 2016)
The mass media which contain of erotic impression can stimulate teenagers who want to know everything about sexual and want to imitate what they hear and look from mass media as a part of learning process.The purpose of this research is to determine the relationship between the erotical exposure on pornmedia to the sexual behaviour of students. The research design is descriptive correlational on subjects totalling 87 people. The instruments used is the scale of the erotical exposure and sexual behaviour scale which contain 46 items on each scale. Trials carried out to 40 people with the validity 0,312 and reliability 0,947 and 0,953. The result of research shows the correlation of rxy = 0,212, p = 0,049 < 0,05 it means that there is a correlation between the erotical exposure on pornomedia with student’s sexual behaviour.